Cloud technologies in the process of higher educational institution IT infrastructure projecting - V. P. Oleksyuk (Academy of Cognitive and Natural Sciences, 2014)
The article investigated the concept of IT infrastructure of higher educational institution. The article described models of deploying of cloud technologies in IT infrastructure. The hybrid model is most recent for higher educational institution. The unified authentication is an important component of IT infrastructure. The author suggests the public (Google Apps, Office 365) and private (Cloudstack, Eucalyptus, OpenStack) cloud platforms to deploying in IT infrastructure of higher educational institution. The purpose of article is to designing individual components of the IT infrastructure of a higher education institution using cloud technology. Task of the research: to analyze the concept of "IT infrastructure", to determine the characteristics of deployment of the cloud technologies and to offer the some components of the IT infrastructure of universities in the traditional and cloud context aspect. The object of the research is IT infrastructure of higher education. The subject of the research is cloud and traditional services as components of the IT infrastructure of the university. Methods: analysis of literature studying the functioning of the IT infrastructure of the university, modeling and design of IT infrastructure. Results: analyzed the concept of "IT infrastructure", "cloud technology", defined characteristics and models of cloud technology deployment, proposed separate components of the IT infrastructure of higher education institutions in the context of "traditional" and "cloud" aspects. Conclusions. The use of cloud technologies in the design of IT infrastructure of universities is an actual and need of the development. The hybrid model is the most appropriate in the deployment of cloud infrastructure of higher educational institution. It is reasonable to use the public (Google Apps and Microsoft Office 365) and private (Cloudstack, Eucalyptus, OpenStack) cloud platform.